Positive electrode material, positive electrode plate and secondary battery
By designing the concentration distribution of element M in the positive electrode material of lithium-ion batteries, compressive stress is formed, the problem of low cycling performance of lithium-ion batteries is solved, and higher cycling stability and rate performance are achieved.
Patent Information
- Application Number
- CN202411976431.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The circulation performance of existing lithium-ion batteries is low, making it difficult to meet the high requirements of electric vehicles and electronic equipment for energy density, safety and circulation performance.
By designing a new positive electrode material, it includes elements M (such as Na, K, Mg, Ca, Sr or Ba), and by controlling the concentration distribution of element M in the particles, the content of element M in the surface area is higher and the content of element M in the central area is lower, thereby forming a compressive stress and suppressing the lattice expansion during charging and discharging.
It improves the cycle stability and rate performance of the positive electrode material, extends the cycle life of the battery, and reduces the DC internal resistance.
Smart Images

Figure CN119764412A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material, a positive electrode sheet and a secondary battery. Background Art
[0002] Lithium-ion batteries have the advantages of high specific energy, high operating voltage, low self-discharge rate, small size, and light weight, and are widely used in various fields such as portable electronic devices, drones, and electric vehicles. With the rapid development of electric vehicles and electronic devices, people have higher and higher requirements on the energy density, safety, and cycle performance of lithium-ion batteries. There is an urgent need to improve the positive electrode materials in lithium-ion batteries to improve the cycle performance of existing lithium-ion batteries. Summary of the invention
[0003] In view of this, in order to solve at least one of the above defects, the present application provides a positive electrode material to improve the cycle stability capacity and cycle performance of the positive electrode material.
[0004] In addition, the present application also provides a positive electrode sheet and a secondary battery using the positive electrode material.
[0005] The present application provides a positive electrode material, including an element M, wherein the element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba; the positive electrode material includes a plurality of particles, wherein a cross section of the particle includes a central region and a surface region, and an energy dispersive spectrometer (EDS) is used to test the cross section of the particle, wherein an average concentration of the element M in the central region is X1, and an average concentration of the element M in the surface region is X2, and X1 and X2 satisfy: 1.2≤X2 / X1≤20; an X-ray diffraction measurement is performed on the positive electrode material, and a unit cell volume of the positive electrode material is
[0006] In some embodiments, 5≤X2 / X1≤15.
[0007] In some embodiments, the lattice strain ε of the positive electrode material is: ε<0.2%.
[0008] In some embodiments, the unit cell parameters of the cathode material are
[0009] In some embodiments, the unit cell parameters of the cathode material are
[0010] In some embodiments, the positive electrode material has a unit cell parameter c / a value greater than 4.95.
[0011] In some embodiments, the concentration of the element M is m, 10 ppm≤m≤400 ppm based on the mass of the positive electrode material.
[0012] In some embodiments, the positive electrode material further includes element N, which is selected from at least one of Zr, Ti, Al, W, Ce or Y. Based on the mass of the positive electrode material, the concentration of element N is n, and n<5000ppm.
[0013] In some embodiments, the concentration m of the element M and the concentration n of the element N satisfy: 1 <n / m<300。
[0014] In some embodiments, the positive electrode material is a single crystal material, the particles include primary particles, and the average particle size of the primary particles is 1 μm to 5 μm.
[0015] In some embodiments, the positive electrode material further includes elements Ni, Co and Mn, and in the X-ray energy spectrum of the positive electrode material, the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material is less than or equal to 0.03.
[0016] In some embodiments, the volume particle size distribution Dv50 of the positive electrode material is 3.0 μm to 5.0 μm.
[0017] In some embodiments, the specific surface area of the positive electrode material is 0.4 m 2 / g to 0.9m 2 / g.
[0018] In some embodiments, the tap density of the positive electrode material is: ρ1>2.0 g / cm 3 .
[0019] In some embodiments, the powder compaction density of the positive electrode material is ρ2: ρ2 ≥ 2.8 g / cm 3 .
[0020] In some embodiments, the general formula of the positive electrode material is: Li x Ni a Co b Q c M (1-a-b-c) O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, a+b+c<1, element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba, and element Q is selected from at least one of Mn and Al.
[0021] The present application also provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode material.
[0022] The present application also provides a secondary battery, including a shell, an electrode assembly, and an electrolyte or an electrolyte, the electrode assembly and the electrolyte or the electrolyte are both located in the shell, the electrode assembly includes a separator and a negative electrode plate, the electrode assembly also includes a positive electrode plate, and the separator is arranged between the positive electrode plate and the negative electrode plate.
[0023] In the present application, the concentration of element M in the particle is controlled to satisfy 1.2≤X2 / X1≤20, so that the content of element M near the surface of the particle is relatively high, and element M increases the unit cell volume of the surface of the particle, while the content of element M near the center of the particle is relatively low, making the unit cell volume in the center of the particle relatively small, thereby forming a compressive stress from the surface to the center of the particle. The compressive stress can inhibit the lattice expansion during the charge and discharge process, thereby improving the gas production performance and long-term cycle performance. At the same time, the unit cell volume of the positive electrode material is controlled. The small unit cell volume means that the distance between atoms or ions in the unit cell is shorter, which enhances the interaction force between atoms or ions (such as Coulomb force, van der Waals force, etc.), thereby increasing the cohesive energy of the crystal, which can further inhibit the volume change of the positive electrode material during the charging and discharging process and improve the cycle stability of the positive electrode material.
[0024] Main component symbols
[0025] The electrode assembly 100 includes a positive electrode sheet 101 , a negative electrode sheet 102 and a separator 103 . BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.
[0027] Figure 2 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.
[0028] Figure 3 This is a scanning electron microscope (SEM) image of the positive electrode material of Example 1 of the present application.
[0029] Figure 4 This is a scanning electron microscope (SEM) image of a high-magnification section of the positive electrode material of Example 1 of the present application.
[0030] Figure 5 This is a distribution diagram of the content of element M inside the particles of the positive electrode material of Example 1 of the present application.
[0031] Figure 6 This is a schematic diagram of the structure of the M element concentration distribution in this application. DETAILED DESCRIPTION
[0032] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0033] An embodiment of the present application provides a secondary battery, comprising a housing, an electrode assembly and an electrolyte. The electrode assembly and the electrolyte are both located in the housing.
[0034] The outer shell can be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), for example, a soft-pack battery. In other embodiments, it can also be a steel shell battery, an aluminum shell battery, etc.
[0035] See also Figure 1 and Figure 2 The electrode assembly 100 includes a positive electrode sheet 101, a negative electrode sheet 102 and a separator 103, wherein the separator 103 is disposed between the positive electrode sheet 101 and the negative electrode sheet 102. Figure 1 During discharge, active ions (such as lithium ions) are deintercalated from the lattice of the negative electrode material of the negative electrode plate 102, pass through the electrolyte through the separator 103, reach the positive electrode plate 101 and are embedded in the lattice of the positive electrode material (such as the lithiated intercalation compound), and generate electrons from the negative electrode plate 102 through the external circuit to the positive electrode plate 101. The reverse movement of the electrons forms an electric current that can be used by electrical appliances. When charging, please refer to Figure 2 , active ions (such as lithium ions) are deintercalated from the lattice of the positive electrode material (such as the lithiated intercalation compound) of the positive electrode plate 101, pass through the isolation membrane 103 through the electrolyte, reach the negative electrode plate 102 and are inserted into the lattice of the negative electrode material.
[0036] In some embodiments, the electrode assembly 100 may be a laminated structure, which is formed by alternately stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102. In other embodiments, the electrode assembly 100 may also be a wound structure, which is formed by stacking the positive electrode sheet 101, the separator 103, and the negative electrode sheet 102 in sequence and then winding them.
[0037] The present application also provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode material.
[0038] An embodiment of the present application provides a positive electrode material, including an element M, wherein the element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba; the positive electrode material includes a plurality of particles, wherein a cross section of the particle includes a central region and a surface region, and an energy dispersive spectrometer (EDS) is used to test the cross section of the particle, wherein an average concentration of the element M in the central region is X1, and an average concentration of the element M in the surface region is X2, and X1 and X2 satisfy: 1.2≤X2 / X1≤20; an X-ray diffraction measurement is performed on the positive electrode material, and a unit cell volume of the positive electrode material is
[0039] In this application, the concentration of element M in the particle is controlled to satisfy 1.2≤X2 / X1≤20, so that the content of element M near the surface of the particle is relatively high, and element M increases the unit cell volume of the surface of the particle, while the content of element M near the center of the particle is relatively low, making the unit cell volume in the center of the particle relatively small, thereby forming a compressive stress from the surface to the center of the particle. The compressive stress can inhibit the change of the lattice volume during the charge and discharge process, thereby improving the gas production performance and long-term cycle performance. At the same time, the unit cell volume of the positive electrode material is controlled A small unit cell volume means that the distance between atoms or ions in the unit cell is shorter, which enhances the interaction force between atoms or ions (such as Coulomb force, van der Waals force, etc.), thereby increasing the cohesive energy of the crystal, which can further inhibit the lattice volume change of the positive electrode material during the charging and discharging process and improve the cycle stability of the positive electrode material.
[0040] When X2 / X1<1.2, the particle surface unit cell volume and the internal unit cell volume are evenly distributed, and the average unit cell volume of the particle is relatively large, which makes it difficult to form a gradient stress field and generate compressive stress, which is not conducive to improving the long-term cycle performance of the secondary battery. When X2 / X1>20, too much element M will be enriched in the surface area of the particle, occupying the lattice lithium site, affecting the transmission and diffusion of lithium ions, and reducing the rate performance of the secondary battery.
[0041] In some embodiments, the ratio of X2 / X1 can be 1.2, 1.5, 2, 5, 7, 9, 10, 12, 14, 15, 16, 18, 20 or any value within the range formed by any two of the above values. The unit cell volume V of the positive electrode material can be
[0042] Or any value within the range formed by any two of the above values.
[0043] In some embodiments, 5≤X2 / X1≤15, It can further improve the rate performance and long-term cycle performance of the positive electrode material.
[0044] In some embodiments, the nickel-lithium mixing ratio of the positive electrode material is 5% to 8%. If the nickel-lithium mixing ratio is controlled within an appropriate range, the positive electrode material can have a better capacity. If the nickel-lithium mixing ratio is greater than 8%, the position of lithium is occupied too much by nickel, which will deteriorate the capacity of the positive electrode material. In some embodiments, the nickel-lithium mixing ratio of the positive electrode material can be 5%, 5.1%, 5.2%, 5.3%, 5.8%, 6%, 6.2%, 6.3%, 6.5%, 7%, 7.3%, 8%, or any value within the range formed by any two of the above values.
[0045] In some embodiments, the value of the unit cell parameter c / a of the positive electrode material is greater than 4.95. The present application further defines that the value of the unit cell parameter c / a is greater than 4.95. When the value of c / a of the positive electrode material is within the above range, the positive electrode material has a suitable interlayer spacing, thereby reducing interlayer stress and improving the stability of the layered structure, which is beneficial to the transmission of lithium ions and reduces the lattice volume change caused by the insertion or extraction of lithium ions. In some embodiments, the value of the unit cell parameter c / a of the positive electrode material can be 4.96, 4.97, 4.99, 5, 5.01, 5.02, 5.03, 5.04, 5.05 or any value within the range composed of any two of the above values. Preferably, the value of the unit cell parameter c / a of the positive electrode material is greater than 4.95 and less than or equal to 5.05.
[0046] In some embodiments, the unit cell parameters of the cathode material are The unit cell parameter a of the positive electrode material is within the above range, indicating that the distance between the atoms in the layer of the positive electrode material is shorter and the material structure is more compact, which is beneficial to reduce the unit cell volume, increase the cohesive energy of the crystal, inhibit the change of the lattice volume of the positive electrode material during the charge and discharge process, and is beneficial to improve the cycle stability of the positive electrode material. This indicates that the distance between atoms in the positive electrode material is long, the unit cell volume is large, and the cohesive energy of the crystal is small, which is not conducive to suppressing the lattice volume change of the positive electrode material during the charge and discharge process. In some embodiments, the unit cell parameter a of the positive electrode material can be
[0047] Or any value within the range formed by any two of the above values. Preferably, the unit cell parameter a of the positive electrode material is greater than or equal to Less than or equal to
[0048] In some embodiments, the unit cell parameters of the cathode material are The smaller the cell parameter c, the smaller the interlayer spacing in the cathode material, which can reduce the cell volume, increase the cohesive energy of the crystal, inhibit the change of the lattice volume of the cathode material during the charge and discharge process, and help improve the cycle stability of the cathode material. This indicates that the interlayer spacing of the positive electrode material is large, resulting in a large unit cell volume and a small crystal cohesive energy, which is not conducive to suppressing the lattice volume change of the positive electrode material during the charge and discharge process. In some embodiments, the unit cell parameter c of the positive electrode material can be Or any value within the range formed by any two of the above values. Preferably, the unit cell parameter c of the positive electrode material is greater than Less than or equal to
[0049] Therefore, the present invention can form compressive stress in the particles of the positive electrode material by controlling the concentration of the element M in the particles of the positive electrode material to satisfy 1.2≤X2 / X1≤20, and then control the unit cell volume of the positive electrode material. Unit cell parameters And the ratio of the unit cell parameter c / a is greater than 4.95, which can enable the particles of the positive electrode material to form a stable crystal structure with high cohesive energy, thereby synergistically forming a stable compressive stress structure, improving the structural stability of the positive electrode material, and inhibiting the lattice volume change formed in the positive electrode material during the charge and discharge process, thereby further improving the cycle stability and rate performance of the positive electrode material.
[0050] In some embodiments, the lattice strain ε of the positive electrode material is: ε<0.2%. By controlling the lattice strain of the positive electrode material within an appropriate range, it is beneficial for the crystal to form a stable compressive stress structure, reduce the crystal volume change caused by lithium ion migration during the charging and discharging process of the secondary battery, inhibit the generation and diffusion of microcracks in the particles of the positive electrode material, thereby improving the stability and cycle performance of the positive electrode material and reducing the direct current internal resistance (DCR) of the positive electrode material. In some embodiments, the lattice strain ε of the positive electrode material can be 0.05%, 0.07%, 0.1%, 0.12%, 0.15%, 0.18% or any value within the range formed by any two of the above values.
[0051] The difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in a grain is the same, and the grains with the same orientation are single crystals. It should be specially noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.
[0052] It can be understood that a single grain in the present application can be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. "Quasi-secondary particles" refer to those formed by the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particles is usually between 1μm and 5μm. In general, the roundness of the particles of "quasi-secondary particles" is lower than that of the above-mentioned conventional "secondary particles".
[0053] In some embodiments, the positive electrode material is a single crystal material, and the particles include primary particles, and the average particle size of the primary particles is 1 μm to 5 μm, which is conducive to the good capacity and rate performance of the positive electrode material, and also has good long-term cycle performance. If the average particle size of the primary particles is small, such as less than 1 μm, the primary particles are severely agglomerated and easily ruptured during the rolling process of the pole piece, increasing the contact surface with the electrolyte, increasing the side reaction, and affecting the long-term performance of the battery; if the average particle size of the primary particles is large, such as greater than 5 μm, the average particle size of the primary particles is large, which will affect the conductivity of the positive electrode material and the transmission of lithium ions, and seriously affect the capacity and rate performance of the positive electrode material. In some embodiments, the average particle size of the primary particles can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any value within the range composed of any two of the above values.
[0054] In some embodiments, based on the mass of the positive electrode material, the concentration of element M is m, 10ppm≤m≤400ppm. The concentration of element M is within the above-mentioned suitable range, which is conducive to making the particles of the positive electrode material contain suitable element M, and making element M maintain a suitable unit cell volume size, and the unit cell volume of the particles is in a contracted state, reducing the cracks generated in the positive electrode material during the long cycle process, further improving the cycle stability of the positive electrode material, and taking into account the positive electrode material has good rate performance and cycle performance. In some embodiments, the concentration of element M can be 10ppm, 50ppm, 80ppm, 100ppm, 120ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm or any value within the range composed of any two of the above values.
[0055] In some embodiments, the positive electrode material further includes element N, and element N is selected from at least one of Zr, Ti, Al, W, Ce or Y. In the above positive electrode material, doping with an appropriate amount of element N can further improve the specific capacity and cycle stability of the positive electrode material.
[0056] In some embodiments, based on the mass of the positive electrode material, the concentration of element N is n, n < 5000ppm. In some embodiments, the concentration of element N can be 10ppm, 100ppm, 200ppm, 500ppm, 600ppm, 800ppm, 1000ppm, 1500ppm, 1700ppm, 1900ppm, 2000ppm, 2500ppm, 2700ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 4800ppm or any value within the range formed by any two of the above values. In some embodiments, the concentration of element N is 1000ppm to 3000ppm.
[0057] In some embodiments, the concentration m of element M and the concentration n of element N satisfy: 1 < n / m < 300. When the concentrations of element M and element N satisfy the above relationship, it is beneficial to improve the cycle stability of the cathode material, and it is also beneficial to improve the rate performance and long-term electrochemical performance of the cathode material. When n / m < 1, the concentration of element N is too small to achieve the effect of improving the growth of the unit cell volume of the particles and cannot improve the performance of the cathode material; when n / m > 300, the concentration of element N is too high, and too much element N will accumulate on the surface layer of the particles, easily causing agglomeration and adhesion of the particles. During the compaction process of preparing the cathode electrode sheet using the cathode material, it is easy to cause cracking of the agglomerated particles, which will increase the side reaction between the electrolyte and the cathode material in the secondary battery and affect the long-term electrochemical performance of the secondary battery. In some embodiments, n / m can be 1.5, 5, 10, 20, 50, 100, 150, 200, 250, 290 or any value within the range formed by any two of the above values. In some embodiments, preferably, the range of n / m is 5 to 150.
[0058] In some embodiments, in the X-ray energy spectrum of the cathode material, the standard deviation of the mass content of each of the elements Ni, Co, and Mn in the cathode material is less than or equal to 0.03. Such a setting is beneficial to make the elements Ni, Co, and Mn in the cathode material evenly distributed, reduce the structural defects of the particles in the cathode material, and is beneficial to promote the segregation of element M to the surface layer region of the particles, so that element M shows a distribution structure with a higher concentration in the surface layer region and a lower concentration in the central region of the particles, thereby being beneficial to maintaining the stability of the compressive stress of the crystal structure and further suppressing the lattice volume change and the generation and expansion of cracks during the charge and discharge process of the cathode material.
[0059] In some embodiments, the volume particle size distribution Dv50 of the cathode material is 3.0 μm to 5.0 μm. When the volume particle size distribution of the cathode material is within the above range, it is beneficial to make the cathode material maintain good discharge capacity and rate performance and improve the electrochemical performance of the cathode material. In some embodiments, the volume particle size distribution Dv50 of the cathode material can be 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm or any value within the range formed by any two of the above values.
[0060] In some embodiments, the specific surface area of the cathode material is 0.4 m 2 / g to 0.9 m 2 / g. When the specific surface area of the cathode material is within the above range, it is beneficial to reduce the contact between the cathode material and the electrolyte, reduce the occurrence of side reactions, and make the cathode material have good discharge capacity. In some embodiments, the specific surface area of the cathode material can be 0.4 m 2 / g, 0.5 m 2 / g, 0.6 m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g or any value within the range formed by any two of the above values.
[0061] In some embodiments, the tap density of the positive electrode material is: ρ1>2.0 g / cm 3 The tap density of the positive electrode material is within a suitable range, which is conducive to improving the compaction of the electrode sheet containing the positive electrode material and improving the energy density of the secondary battery. In some embodiments, the tap density of the positive electrode material can be 2.5 g / cm 3 、3.0g / cm 3 , 3.5g / cm 3 , 4.0g / cm 3 4.5g / cm 3 , 5.0g / cm 3 Or any value within the range formed by any two of the above values.
[0062] In some embodiments, the powder compaction density of the positive electrode material is ρ2: ρ2 ≥ 2.8 g / cm 3 The compaction density of the positive electrode material powder is within a suitable range, which is conducive to further improving the compaction degree of the electrode sheet containing the positive electrode material and improving the energy density of the secondary battery. In some embodiments, the compaction density of the positive electrode material powder can be 2.8 g / cm 3 、3.0g / cm 3 、3.2g / cm 3 、3.8g / cm 3 , 4g / cm 3 4.5g / cm 3 Or any value within the range formed by any two of the above values.
[0063] In some embodiments, the general formula of the positive electrode material is: Li x Ni a Co b Q c M (1-a-b-c)O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, a+b+c<1, element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba, and element Q is selected from at least one of Mn and Al. It should be noted that after the M element enters the transition metal layer of the positive electrode material and occupies the site of the main element, the M element will expand the distance between the transition metal layers, thereby increasing the unit cell volume; when the M element is enriched close to the surface of the grain, the unit cell volume of the surface area of the grain will be larger than the unit cell volume of the center area of the grain, and the stress in the surface area of the grain is larger, thereby generating compressive stress toward the center of the grain, thereby causing the grain to shrink from the surface to the center of the grain.
[0064] The present application also provides a method for preparing a positive electrode material, comprising the following steps:
[0065] S1. Prepare a mixed salt solution containing Ni, Co and Q elements according to the ratio of Ni:Co:Mn; then add a target doping salt solution containing element M to the mixed solution according to the target doping ratio to obtain a precursor solution, wherein element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba. Element Q is selected from at least one of Mn and Al.
[0066] In this step, the raw materials containing Ni, Co, and Q elements and the salt solution containing element M can be independently selected from at least one of sulfates, chlorides, and nitrates, and the salt solution of nickel can be selected from at least one of nickel chloride, nickel sulfate, nickel nitrate, nickel carbonate, nickel oxalate and nickel acetate, metal raw materials, and ternary material recycled materials.
[0067] In this step, in the mixed salt solution, the molar ratio of Ni:Co:Q is (50-98):(0-20):(0-30), and the contents of Co and Q in the mixed salt solution are not 0. In the precursor solution, the molar percentage of element M is 0.01 mol% to 0.05 mol%.
[0068] S2. The precursor solution prepared in step S1 is prepared into an oxide precursor by a spray pyrolysis method, and the oxide precursor is crushed to have a crushed particle size D50 of 2.0 μm to 4.0 μm.
[0069] In this step, the cathode material powder obtained from the precursor at this particle size is less and more round. In the spray pyrolysis method, the precursor solution is atomized and then passes through the dehydration temperature zone and the pyrolysis temperature zone in turn to obtain the cathode material precursor. The spray pyrolysis atomization flow rate V satisfies: 300L / h<V<700L / h, the dehydration temperature zone temperature is 300℃~500℃, the spray solution in the dehydration temperature zone The material residence time is 2-10s, the pyrolysis temperature zone temperature is 500℃~850℃, the spray solution in the pyrolysis temperature zone The material residence time is 2-20s, and the mixed solution after spray atomization in the dehydration temperature zone is quickly dehydrated, which promotes the enrichment of trace elements M on the surface of the dehydrated particles. In the pyrolysis temperature zone, the dehydrated particles after spray atomization are finally pyrolyzed into oxide precursor particles. The higher the pyrolysis temperature, the better the uniformity of the distribution of Ni, Co, and Mn elements inside the particles.
[0070] S3. The crushed oxide precursor is uniformly mixed with a lithium source and a compound containing element N, and then sintered once; the sintered positive electrode material is air flow crushed, and the crushing pressure P satisfies: 200Kpa<P<500Kpa, and the crushing particle size D50 is controlled within 3.0μm to 5.0μm to obtain the material.
[0071] Compounds containing element N can be Zr(NO3)4, ZrCl4, ZrO2, NH4ZrO3, CH4O 10 Zr3, Zr(HPO4)2, Zr(OH)4, Zr(SO4)2, Zr(CH3COO)4, TiO2, Ti2O3, TiCl4, Ti3(PO4)4, Ti(NO3)4, Ti(SO 4)2. AlCl3, Al2O3, Al(OH)3, NaAlO2, C6H9AlO6, AlOOH, Al2(SO4)3, Al(NO3)3, WO2, WO3, Na2WO4, (NH4) 10 (W 12 O 41 ), W2O5, Ce(NO3)3, Ce2(SO4)3, Ce2(C2O4)3, C3Ce2O9, Y(C2H3O2)3), Y2O3, YPO4, Y2(CO3)3, Y(NO3)3, Y2(SO4)3, at least one of the following.
[0072] The lithium source is at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate, and the molar ratio of lithium in the lithium source to the total of nickel, cobalt and manganese in the positive electrode material precursor is 0.98-1.10; the primary sintering temperature is 900°C-1000°C, and the primary sintering time is 4h-20h.
[0073] In this step, the crushed particle size in this particle size range corresponds to the precursor D50 particle size range, and the particles are easily crushed.
[0074] S4. The material obtained after the pulverization in step S3 is uniformly mixed with a coating agent and subjected to secondary sintering, wherein the coating agent contains element N, and the sintered product is screened and demagnetized to obtain a positive electrode material.
[0075] The coating agent is coated on the surface of the material. This process is to improve the electrochemical properties of the material through coating.
[0076] The coating agent can be Zr(NO3)4, ZrCl4, ZrO2, NH4ZrO3, CH4O 10 Zr3, Zr(HPO4)2, Zr(OH)4, Zr(SO4)2, Zr(CH3COO)4, TiO2, Ti2O3, TiCl4, Ti3(PO4)4, Ti(NO3)4, Ti(SO 4)2. AlCl3, Al2O3, Al(OH)3, NaAlO2, C6H9AlO6, AlOOH, Al2(SO4)3, Al(NO3)3, WO2, WO3, Na2WO4, (NH4) 10 (W 12 O 41 ), W2O5, Ce(NO3)3, Ce2(SO4)3, Ce2(C2O4)3, C3Ce2O9, Y(C2H3O2)3), Y2O3, YPO4, Y2(CO3)3, Y(NO3)3, Y2(SO4)3, at least one of the following.
[0077] The secondary sintering temperature is 300° C. to 600° C., and the secondary sintering time is 4 h to 20 h.
[0078] Negative electrode
[0079] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.
[0080] The negative electrode current collector includes copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, or any combination thereof.
[0081] The negative electrode current collector includes copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, a polymer substrate coated with a conductive metal, or any combination thereof.
[0082] The negative electrode active material includes a material that reversibly intercalates / deintercalates lithium ions. In some embodiments, the material that reversibly intercalates / deintercalates lithium ions includes a carbon material. In some embodiments, the carbon material can be any carbon-based negative electrode active material commonly used in lithium-ion rechargeable batteries. In some embodiments, the carbon material includes, but is not limited to: crystalline carbon, amorphous carbon, or a mixture thereof. Crystalline carbon can be amorphous, flaky, flake-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0083] In some embodiments, the negative electrode active material layer includes a negative electrode active material. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. In some embodiments, the negative electrode active material includes, but is not limited to: lithium metal, structured lithium metal, natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or any combination thereof. The silicon-carbon composite refers to a composite containing at least about 5 wt% silicon based on the weight of the silicon-carbon negative electrode active material.
[0084] In some embodiments, the negative electrode active material comprises at least one of artificial graphite, natural graphite, hard carbon, soft carbon, silicon alloy, or silicon oxide.
[0085] When the negative electrode includes a silicon-carbon compound, based on the total weight of the negative electrode active material, silicon:carbon=about 1:10-10:1, and the median particle size Dv of the silicon-carbon compound is 50 The negative electrode active material layer may be formed by a method such as evaporation, sputtering, or plating. When the negative electrode includes lithium metal, the negative electrode active material layer may be formed by, for example, a spherical and twisted conductive skeleton and metal particles dispersed in the conductive skeleton. In some embodiments, the spherical and twisted conductive skeleton may have a porosity of about 5% to about 85%. In some embodiments, a protective layer may also be provided on the lithium metal negative electrode active material layer.
[0086] In some embodiments, the negative electrode active material layer may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0087] In some embodiments, the conductive material includes, but is not limited to: a carbon-based material, a metal-based material, a conductive polymer, or a mixture thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0088] In some embodiments, the current collector includes, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof.
[0089] The negative electrode can be prepared by a preparation method known in the art. For example, the negative electrode can be obtained by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition, and coating the active material composition on a current collector. In some embodiments, the solvent may include water, etc., but is not limited thereto.
[0090] Isolation film
[0091] The material and shape of the separator used in the secondary battery of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0092] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.
[0093] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.
[0094] The binder is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).
[0095] Electrolyte
[0096] According to some embodiments of the present application, the electrolyte includes an organic solvent, a lithium salt, and optional additives.
[0097] The organic solvent in the electrolyte of the present application may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present application is not limited, and it can be any electrolyte known in the prior art. The additive of the electrolyte according to the present application can be any additive known in the prior art that can be used as an electrolyte additive. In some embodiments, the organic solvent includes, but is not limited to: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or ethyl propionate (EP).
[0098] In some embodiments, the organic solvent includes an ether solvent, for example, at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to: lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), bistrifluoromethanesulfonyl imide lithium LiN(CF3SO2)2 (LiTFSI), bis(fluorosulfonyl)imide lithium Li(N(SO2F)2)(LiFSI), lithium bis(oxalate borate) LiB(C2O4)2 (LiBOB) or lithium di(oxalate borate) LiBF2(C2O4) (LiDFOB). In some embodiments, the additive includes at least one of fluoroethylene carbonate and adiponitrile.
[0099] According to some embodiments of the present application, the secondary battery of the present application includes, but is not limited to: a lithium ion battery. In some embodiments, the secondary battery includes a lithium ion battery.
[0100] The present application also applies secondary batteries to electronic devices to power loads in the electronic devices. The electronic devices of the present application are not particularly limited. In some embodiments, the electronic devices of the present application include, but are not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0101] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.
[0102] Example 1
[0103] In this embodiment, the positive electrode material is prepared according to the following method:
[0104] (1) Nickel chloride, cobalt chloride and manganese chloride were weighed and added into water to prepare a mixed salt solution in a molar ratio of Ni:Co:Mn=60:10:30, and a hydrochloride solution of K with a molar percentage of 0.01 mol% was added into the mixed salt solution to obtain a precursor solution.
[0105] (2) The precursor solution obtained in step (1) is atomized and then passed through a dehydration temperature zone and a pyrolysis temperature zone to obtain a positive electrode material precursor (Ni 0.599 Co 0.1 Mn 0.3 K 0.001 O), wherein the atomization flow rate is 500 L / h, the dehydration temperature zone is 500° C., the material residence time in the dehydration temperature zone is 5 s, the pyrolysis temperature zone is 650° C., the material residence time in the pyrolysis temperature zone is 8 s, the precursor is airflow crushed, the crushing pressure is 0.35 kPa, and a precursor crushed material with a particle size D50=3.77 μm is obtained.
[0106] (3) 600 g of the precursor crushed material of step (2) was uniformly mixed with 252 g of lithium carbonate and 2.0 g of Y2O3 (dopant), sintered at 970°C for 20 h in an oxygen atmosphere, and the sintered product was crushed to obtain a crushed material with a particle size of D50 = 3.89 μm.
[0107] (4) 600 g of the crushed material of step (3) was preliminarily mixed with 1.5 g of WO3 (coating), sintered at 400°C for 20 h in an oxygen atmosphere, and the obtained material was sieved to obtain a positive electrode material.
[0108] Preparation method of button half-cell:
[0109] The specific method is as follows: the positive electrode material, conductive carbon black, and PVDF are weighed in a mass ratio of 93:5:2, N-methyl-2-pyrrolidone (NMP) is added at a solid content of 50%, and a high-speed disperser is used to adjust the viscous slurry, which is evenly coated on aluminum foil with a scraper, and then dried in an oven at 80°C, rolled, and cut into positive electrode sheets with a diameter of 14 mm. A 16 mm lithium sheet is used as the negative electrode sheet, a Celgard polypropylene film is used as the separator, and a carbonate solution of LiPF6 with a concentration of 1 mol / L is used as the electrolyte. The assembly is carried out in a glove box filled with argon to obtain a button-type half-cell.
[0110] Example 2
[0111] The difference from Example 1 is that the molar percentage of the K hydrochloride solution added to the mixed solution in step (1) is 0.003 mol %; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0112] Example 3
[0113] The difference from Example 1 is that the molar percentage of the K hydrochloride solution added to the mixed solution in step (1) is 0.03 mol %; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0114] Example 4
[0115] The difference from Example 1 is that in step (2), the pyrolysis temperature zone of the spray pyrolysis method is 550° C.; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0116] Example 5
[0117] The difference from Example 1 is that in step (2), the pyrolysis temperature zone of the spray pyrolysis method is 750° C.; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0118] Example 6
[0119] The difference from Example 1 is that the sintering temperature in step (3) is 955° C.; the remaining preparation steps are the same as those in Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0120] Example 7
[0121] The difference from Example 1 is that in step (3), the primary sintering temperature is 985° C.; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0122] Example 8
[0123] The difference from Example 1 is that in step (1), a mixed hydrochloride solution is prepared according to the molar ratio of Ni:Co:Mn=50:20:30; in step (3), the primary sintering temperature is 980°C; and the remaining preparation steps are the same as in Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0124] Example 9
[0125] The difference from Example 1 is that in step (1), a mixed hydrochloride solution is prepared according to the molar ratio of Ni:Co:Mn=70:10:20; in step (3), 600g of the positive electrode material precursor powder, 268g of lithium hydroxide and 2.0g of Y2O3 (dopant) are uniformly mixed, and the primary sintering temperature is 900°C; the remaining preparation steps are the same as in Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0126] Example 10
[0127] The difference from Example 1 is that in step (1), a mixed hydrochloride solution is prepared according to the molar ratio of Ni:Co:Mn=80:10:10; in step (3), 600g of the positive electrode material precursor powder, 268g of lithium hydroxide and 2.0g of Y2O3 (dopant) are uniformly mixed, and the primary sintering temperature is 740°C; the remaining preparation steps are the same as in Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0128] Embodiment 11
[0129] The difference from Example 1 is that in step (1), a mixed hydrochloride solution is prepared according to the molar ratio of Ni:Co:Mn=90:6:4; in step (3), 600g of the positive electrode material precursor powder, 268g of lithium hydroxide and 2.0g of Y2O3 (dopant) are uniformly mixed, and the primary sintering temperature is 740°C; the remaining preparation steps are the same as in Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0130] Example 12
[0131] The difference from Example 1 is that in step (1), a hydrochloride solution of Sr with a molar percentage of 0.01 mol% is added to the mixed solution; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0132] Example 13
[0133] The difference from Example 1 is that in step (1), a 0.01 mol % Mg hydrochloride solution is added to the mixed solution; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0134] Embodiment 14
[0135] The difference from Example 1 is that the dopant added in step (3) is ZrO2, and the added amount is 1.8 g; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0136] Embodiment 15
[0137] The difference from Example 1 is that the dopant added in step (3) is Al2O3, and the added amount is 1 g; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0138] Example 16
[0139] The difference from Example 1 is that the molar percentage of the K hydrochloride solution added to the mixed solution in step (1) is 0.001 mol %; the remaining preparation steps are the same as those in Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0140] Embodiment 17
[0141] The difference from Example 1 is that in step (2), the pyrolysis temperature zone of the spray pyrolysis method is 850° C.; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0142] Embodiment 18
[0143] The difference from Example 1 is that in step (1), a mixed hydrochloride solution is prepared according to the molar ratio of Ni:Co:Al=60:10:30; the remaining preparation steps are the same as Example 1. The specific performance parameters of the positive electrode material are shown in Table 1 and Table 2.
[0144] Comparative Example 1
[0145] (1) Nickel chloride, cobalt chloride, and manganese chloride were weighed and added to water to prepare a mixed hydrochloride solution in a molar ratio of Ni:Co:Mn=60:10:30, and the solution was added to a reactor at 55° C., and 0.01 mol % of NaOH and NH 3 ·H 2 O were used as precipitants and chelating agents to perform a coprecipitation reaction for 36 hours, thereby obtaining Ni 0.599 Co 0.1 Mn 0.3 Na 0.001 (OH)2 precursor, the precursor was dried at 80°C for 12 hours and then dried again at 110°C for 12 hours.
[0146] (2) 600 g of the precursor, 262 g of lithium carbonate and 2.0 g of Y2O3 (dopant) were uniformly mixed, and sintered at 970°C for 20 h in an oxygen atmosphere. The sintered product was crushed to obtain a crushed material with a particle size of D50 = 3.3 μm-4.2 μm.
[0147] (3) 600 g of the crushed material was preliminarily mixed with 1.5 g of WO3 (coating agent), sintered at 400°C for 20 h in an oxygen atmosphere, and the obtained material was sieved to obtain a finished product. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0148] Comparative Example 2
[0149] The difference from Comparative Example 1 is that in step (2), 600 g of the precursor, 262 g of lithium carbonate, 2.0 g of Y2O3 (dopant), and 1 g of K(OH) are uniformly mixed; the remaining preparation steps are the same as those of Comparative Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0150] Comparative Example 3
[0151] The difference from Example 1 is that in step (1), the proportion of K hydrochloride solution added to the mixed hydrochloride solution is 0; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0152] Comparative Example 4
[0153] The difference from Example 1 is that in step (1), the molar percentage of the K hydrochloride solution added is 0.05 mol %; the remaining preparation steps are the same as those of Example 1. The specific performance parameters of the positive electrode material are shown in Tables 1 and 2.
[0154] The performance of the positive electrode materials prepared in the examples and comparative examples was tested using the following test methods and battery performance test methods.
[0155] Test method:
[0156] 1. The test method for the concentration of M element and main element is as follows:
[0157] Using Agilent 5110ICP-OES equipment, 0.3g of positive electrode material sample was added with aqua regia for digestion, and the mother liquor was obtained after cooling and constant volume. 1mL of the mother liquor was diluted 100 times to test the element content of the main elements (Li / Ni / Co / Mn), and the mother liquor was tested for the M element content.
[0158] The test method for the concentration distribution of M element is as follows:
[0159] The test method for the average concentration X1 of the element M in the center area and the average concentration X2 in the surface area of the positive electrode material particles is as follows: use a Hitachi ion cutting instrument to prepare a cross-section sample, use a Hitachi S4800 scanning electron microscope to select a suitable cross-section field of view, and then use EDS to perform line scanning or point scanning on the particle cross section within the 5k field of view. For example, the point scanning method can be used to measure the content of the element M at 10 positions (generally at least 5 points) in the center area of the particle cross section, and the content of the element M is summed and averaged to obtain X1; measure the content of the element M at 10 positions in the surface area of the particle cross section, and the content of the element M is summed and averaged to obtain X2. Figure 6 As shown in the particle cross-sectional view, the radius of the particle is L, the area from the center of the particle to the distance L / 2 from the center of the particle is the central area, and the area from the position L / 2 of the particle to the surface of the particle is the surface area. When the positive electrode material contains two or more elements M, X1 and X2 of each element M are measured separately, and the X2 / X1 value of the corresponding element is calculated accordingly.
[0160] For point scanning and line scanning, combined Figure 6 The instructions are as follows:
[0161] Scan: In the center area ( Figure 6 5-10 points are selected for EDS measurement (inside the dotted circle shown in the figure), and the average value is taken to obtain the X1 value; in the surface area ( Figure 6 Select 5-10 points (outside the dotted circle shown) for EDS measurement and take the average value after measurement to get the X2 value.
[0162] Line scan: In the central area (i.e. Figure 6 At least three line positions are randomly selected for line scanning (inside the dotted circle shown in the figure), and the average value is taken after measurement to obtain the X1 value; the surface area (i.e. Figure 6 At least three line positions are randomly selected for line scanning (outside the dotted circle shown in the figure), and the average value is taken after measurement to obtain the X2 value. In actual testing, point scanning and line scanning can also be used in combination.
[0163] 2. The test method for the mass content of Ni, Co and Mn elements is as follows:
[0164] The cross-section samples were prepared by using a Hitachi ion cutting instrument, and the particle cross-section field was selected by using a Hitachi S4800 scanning electron microscope. Then, EDS was used to scan the cathode material precursor or cathode material in the field of view at a magnification of 3K at 10 randomly selected points (no less than 3 points in the central area and the surface area) to test the Ni, Co, and Mn contents of the cathode material precursor or cathode material. The standard deviation and range of the mass content of each element Ni, Co and Mn were statistically analyzed to characterize the uniformity of the distribution of Ni, Co, and Mn elements.
[0165] 3. The test methods for unit cell volume, unit cell parameters (a, c), lithium-nickel mixing, lattice strain and grain size are as follows:
[0166] The test was carried out using a Rigaku XRD diffractometer in the range of 10°-70° at a parameter of 1° / min and a step size of 0.005°. The tested XRD spectra were then Rietveld refined by GASA to obtain information such as unit cell volume, unit cell parameters (a, c), lithium-nickel mixing, grain size and peak shape parameters. The lattice strain was calculated based on the obtained peak shape parameters according to the Scherrer formula.
[0167] 4. The volume particle size D50 test method of the positive electrode material is as follows:
[0168] The particle size of the material was tested using Malvern laser particle size tester MS 3000; the specific method was: weigh the sample weight <2g, add 20mL of pure water and mix thoroughly, add 2-3 drops of 3% sodium hexametaphosphate dispersant, ultrasonically stir for 30s, and the shading degree was 8-15%.
[0169] 5. The specific surface area test method is as follows:
[0170] The specific surface area was tested using an American Micrometer specific surface area instrument: the test was performed after degassing at 300°C in vacuum for 1 hour.
[0171] 6. The tap density test method is as follows:
[0172] The tap density was tested using a Quantachrome tap density meter: vibration frequency 260 times / min, vibration number 3000 times, vibration amplitude 3 mm ± 0.1 mm, sample mass measuring cylinder 23-25 ml.
[0173] 7. The powder compaction density test method is as follows:
[0174] The compaction density of the powder was tested using a compaction density meter: the pressure was maintained at 6t for 30s.
[0175] 8. The test method for the average particle size of primary particles is as follows:
[0176] The SEM images of the positive electrode materials were taken using Hitachi's S4800 scanning electron microscope in areas where the particles were evenly dispersed and less agglomerated. The magnification was 3k times, and the number of primary particles in a single SEM was not less than 200. The Nano Measure software was selected to open the taken SEM image, and the 2 grids in the image ruler were measured as the measuring ruler. The size of the single crystal primary particles in the SEM image was measured using the cross-hatch method, and the number of statistics was not less than 400. The average size in the final output report was the average particle size of the primary particles.
[0177] 9. Electrochemical performance test:
[0178] a. Preparation of electrochemical performance test samples:
[0179] Button battery production:
[0180] ① Ingredients: NCM:SP:5% PVDF glue = 93:5:2 = 9.3g:0.5g:4.0g, NMP = 9g, stir at high speed to disperse evenly.
[0181] ② Coating and drying: Evenly coat the slurry on 20μm thick aluminum foil with a 210um coater, set the coating length to the maximum length of the coater, cut the back half of the electrode and put it into a 100℃ forced air drying oven to dry for more than 1.5 hours.
[0182] ③ Rolling, punching and drying: When rolling, adjust the roller machine to 1 roller gap and roll 3 times; use a 14mm punching machine to punch holes, weigh, and place in a vacuum drying oven for vacuum drying at 85°C for more than 8 hours.
[0183] ④ Button battery (LIR2016) assembly: positive electrode shell - 2 drops of electrolyte - positive electrode sheet (14mm) - 3 drops of electrolyte - 20μm diaphragm - 2 drops of electrolyte Lithium sheet-150μm nickel foam-negative electrode shell (dried at 50℃), after the battery is assembled, it is sealed and taken out of the glove box for testing.
[0184] b. Button battery test:
[0185] After standing for 12 hours, perform the battery test according to the following system:
[0186] The test voltage of the positive electrode materials prepared in Examples 1-7, Examples 12-18, and Comparative Examples 1-4 was 3-4.4V; the test voltage of the positive electrode material prepared in Example 8 was 3-4.45V; the test voltage of the positive electrode material prepared in Example 9 was 3-4.3V; the test voltage of the positive electrode material prepared in Examples 10 / 11 was 3-4.25V;
[0187] 0.1C charge and 0.1C discharge for 2 weeks, constant voltage cut-off current 0.005C, the first cycle capacity and the first cycle coulombic efficiency were measured.
[0188] 0.5C charge and 2C discharge for 1 week, constant voltage cut-off current 0.05C, the ratio of the measured capacity to the first cycle capacity is the 2C capacity retention rate;
[0189] The battery was cycled at 0.5C charge and 1C discharge for 50 cycles with a constant voltage cutoff current of 0.05C. The ratio of the measured capacity to the first cycle capacity is the 50-cycle capacity retention rate.
[0190] Charge at 0.1C and discharge at 0.1C to 3.7V. After standing for 5h, place the battery at 25℃ and then discharge at 2C for 30s. Take a point every 0.1s and calculate the average internal resistance of 30s as DCR (DC internal resistance).
[0191] Table 1
[0192]
[0193] Table 2
[0194]
[0195] Table 3
[0196]
[0197] It can be seen from Tables 1 to 3 above that, compared with Comparative Examples 1 to 4, in Examples 1 to 18, when the concentration X2 / X1 of the element M in the prepared positive electrode material satisfies a specific range and the unit cell volume V of the particles satisfies a specific range, the positive electrode material has good specific capacity and lower DC internal resistance, and also has excellent first-cycle capacity, first-cycle coulomb efficiency and cycle capacity retention rate.
[0198] Compared with Example 1, Comparative Example 1 adopts the coprecipitation method to prepare the positive electrode material precursor, and the obtained positive electrode material is characterized, and its unit cell volume is At the same time, in Comparative Example 1, element M is not doped, the DC internal resistance of the positive electrode material is high, and the first efficiency and cycle stability are low.
[0199] Compared with Example 1, Comparative Example 2 adopts a co-precipitation method to prepare a positive electrode material precursor, and solid-phase doping of K element is performed in step (3). Characterization shows that the obtained positive electrode material has a relatively uniform distribution of element K inside the positive electrode material particles, a relatively high DC internal resistance, and a relatively low first efficiency and cycle stability.
[0200] Compared with Example 1, Comparative Example 3 adopts spray treatment and pyrolysis treatment to prepare the positive electrode material precursor. No K element is added in step (1). The unit cell volume in the positive electrode material is larger, the DC internal resistance of the positive electrode material is higher, and the first efficiency and cycle stability are lower.
[0201] Compared with Example 1, Comparative Example 4 adopts spray treatment and pyrolysis treatment to prepare the positive electrode material precursor, and adds soluble K salt in step (1), and increases the amount of soluble K salt added in step (1) to 0.05 mol%. The positive electrode material obtained by characterization has a relatively high concentration of K element in the surface area and the central area of the particles of the positive electrode material, a large unit cell volume in the positive electrode material, a high DC internal resistance of the positive electrode material, and a low first efficiency and cycle stability.
[0202] See also Figure 3 and Figure 4 In the scanning electron microscope image and the scanning electron microscope image of the high-power section of the positive electrode material prepared in Example 1, the particles are evenly distributed. Figure 5 , the content of element M in the surface area and the central area of the particle is different.
[0203] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises an element M, wherein the element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba; the positive electrode material comprises a plurality of particles, the cross section of the particles comprises a central region and a surface region, and the cross section of the particles is tested by an energy spectrometer, and the average concentration of the element M in the central region is X1, and the average concentration of the element M in the surface region is X2, and X1 and X2 satisfy: 1.2≤X2 / X1≤20; the positive electrode material is measured by X-ray diffraction, and the unit cell volume of the positive electrode material 2. The positive electrode material according to claim 1, characterized in that 5≤X2 / X1≤15.
3. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The lattice strain ε of the positive electrode material is: ε<0.2%; (2) The lithium-nickel mixing ratio of the positive electrode material is 5% to 8%; (3) Unit cell parameters of the positive electrode material (4) Unit cell parameters of the positive electrode material (5) The value of the unit cell parameter c / a of the positive electrode material is greater than 4.
95.
4. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) Based on the mass of the positive electrode material, the concentration of the element M is m, 10ppm≤m≤400ppm; (2) The positive electrode material further includes element N, and the element N is selected from at least one of Zr, Ti, Al, W, Ce or Y. Based on the mass of the positive electrode material, the concentration of the element N is n, and n<5000 ppm; (3) The concentration m of the element M and the concentration n of the element N satisfy: 1 <n / m<300。 5. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, the particles include primary particles, and the average particle size of the primary particles is 1 μm to 5 μm.
6. The positive electrode material according to claim 1, characterized in that The positive electrode material also includes elements Ni, Co and Mn. In the X-ray energy spectrum of the positive electrode material, the standard deviation of the mass content of each element Ni, Co and Mn in the positive electrode material is less than or equal to 0.
03.
7. The positive electrode material according to any one of claims 1 to 6, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The volume particle size distribution Dv50 of the positive electrode material is 3.0 μm to 5.0 μm; (2) The specific surface area of the positive electrode material is 0.4 m 2 / g to 0.9m 2 / g; (3) The tap density ρ1 of the positive electrode material: ρ1>2.0 g / cm 3 ; (4) The powder compaction density of the positive electrode material ρ2: ρ2 ≥ 2.8 g / cm 3 .
8. The positive electrode material according to claim 1, characterized in that The general formula of the positive electrode material is: Li x Ni a Co b Q c M (1-a-b-c) O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, a+b+c<1, the element M is selected from at least one of Na, K, Mg, Ca, Sr or Ba, and the element Q is selected from at least one of Mn and Al.
9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes the positive electrode material according to any one of claims 1 to 8.
10. A secondary battery, comprising a housing, an electrode assembly, and an electrolyte or an electrolyte, wherein the electrode assembly and the electrolyte or the electrolyte are both located in the housing, and the electrode assembly comprises a separator and a negative electrode sheet, characterized in that: The electrode assembly further comprises the positive electrode sheet as claimed in claim 9, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.
Citation Information
Cited By
Positive electrode material, positive electrode sheet, and secondary battery
WO2026138706A1